Analisis Implementasi Manajemen Zakat Infaq dan Sedekah Dalam Rangka Meningkatkan Akuntanbilitas dan Kompetensi Pengelolaan Zakat Di LAZISMU Wilayah Bengkulu - Jessy Obastika; Jafril Khalil (Jurnal Ilmiah Ekonomi Islam, 2023)
LAZISMU is an institution entrusted with managing Zakat, Infaq, Alms, and humanitarian funds. In its management, LAZISMU Bengkulu Region is managed by an appointed amil without unique criteria. This study aims to analyze the implementation of operational management and the accountability and competence of the LAZISMU Supervisory Board and Management Board in the Bengkulu Region. The research is expected to correct the weaknesses in the management of the LAZISMU Bengkulu Region. This research is a qualitative descriptive study with data analysis using NVIVO 12 PLUS. Based on field findings, it is known that the leadership of LAZISMU Bengkulu has leadership characteristics in the style of Rasulullah, namely Amanah (trustworthiness), as indicated by the accountability of financial reports with internal and external audits, as evidenced by the results of an external audit of financial reports for 2021 with the WTP (Unqualified) predicate. Tabligh (convey) that LAZISMU distribution is in accordance with asnaf, although not so much has been given and received. Fatannah (intelligent) that leaders at LAZISMU are qualified according to their functions and abilities in management even though they are not in accordance with their educational background.